An Efficient and Safe Herpes Simplex Virus Type 1 Amplicon Vector for Transcriptionally Targeted Therapy of Human Hepatocellular Carcinomas - Lam, Paula YP; Sia, Kian Chuan; Khong, Jenn H; Geest, Bart De; Lim, Kar S; Ho, Ivy AW; Wang, Grace Y; Miao, Lv; Huynh, H; Hui, Kam M (Molecular therapy, 2007)
Our previous studies have shown that transgene expression could be targeted to proliferating cells when cell cycle transcriptional regulatory elements were incorporated into herpes simplex virus type 1 (HSV-1) amplicon backbone vectors. In the study reported here, we further demonstrated the transcriptional activation of transgene expression in association with the onset of cellular proliferation using the mouse partial hepatectomy model. Moreover, transcriptional regulation could be rendered specific to human hepatocellular carcinoma (HCC) cells by inserting the chimeric gene Gal4/NF-YA under the regulation of the HCC-specific hybrid promoter. The hybrid promoter, which consists of four copies of the apolipoprotein E (ApoE) enhancer element inserted upstream of the human α1-antitrypsin(hAAT) promoter, induced an higher level of transcription than other liver-specific promoters such as alpha-fetoprotein (AFP) and albumin (Alb) promoter. As a consequence, the enhancement of tissue-specific expression in the context of Gal4/NF-YA fusion proteins enabled the monitoring of transgene expression using a bioluminescence imaging system. Furthermore, these vectors have been shown to be non-toxic and exhibited potent infectivity for proliferating primary HCC cells and HCC cell lines. Together, these results demonstrated that the new hybrid vectors could provide options for the design of safe and efficient systemic gene therapeutic strategies for human HCC.